Management responses in Belize and Honduras, as stony coral tissue loss disease expands its prevalence in the Mesoamerican reef - Lee Hing, Catherine; Guifarro, Zara; Dueñas, Damaris; Ochoa, Gabriela; Nunez, Alicia; Forman, Kirah; Craig, Nicole; McField, Melanie (Frontiers in Marine Science, 2022)
Stony Coral Tissue Loss Disease (SCTLD) has affected Caribbean coral reef colonies since it was first detected in Florida in 2014. Its rapid spread and virulent nature are a major concern to coastal nations in the Caribbean Sea. Belize and Honduras have approached their management and strategies in somewhat different ways, but with the same goal of evaluating and controlling the spread and reducing mortality rates of their coral colonies. They both used amoxicillin trihydrate powder with Coral Ointment Base2B which proved effective in halting the spread of the disease and lowered mortality rates in treated corals. In addition to treatment, both countries have continued to monitor the extent of the disease, entering the data into the collaborative disease tracker platform on AGRRA.org. Between October 2020 and November 2021, a total of 14,495 corals from 29 species were assessed at sites in Belize and Honduras that were affected by SCTLD. The overall prevalence (all coral species) of SCTLD at these sites was 14%. Three species (Meandrina meandrites, Dendrogyra clyindrus and Dichocoenia stokesi) were in the top affected species in both countries, with 42%, 38% and 32% SCTLD prevalence, respectively. The sharing of information allowed Belize and Honduras to be relatively prepared for the onset of SCTLD in their waters through a series of monitoring and intervention actions. Although the treatment has proved to be somewhat effective, it is time and labor intensive. Reducing other well-known anthropogenic stressors, including sewage, dredging is key to the overall strategy to recover reef health.